Respostas
respondido por:
1
Resposta:
Explicação passo-a-passo:
a)
isolar x de x+y-6=0 ------->x= - y+6
substituir y de ambos lados
x+y-6-y= 0-y
simplificar;
x- 6 = - y
adicionar 6 a ambos lados
x - 6 + 6= -y + 6
simplificar
x=-Y+6
substituir x=-y+6
(-y + 6 - y + 8= 0)
simplificar:
(- 2y + 14 = 0)
isolar y de -2y +14=0--------> y= 7
para x = -y+6
substituir y = 7
x= -7+6
simplificar:
x=-1
Resposta:
x= - 1
y= 7
b)
simplificar
8y-16=-21
simplificar:
resposta:
bons estudos...
navegante2014:
de sua nota por favor
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás